Seroprevalence and associated risk factors for foot and mouth disease virus seropositivity in cattle in selected districts of Gamo zone, Southern Ethiopia - Shurbe, Mesfin; Simeon, Bekahegn; Seyoum, Wasihun; Muluneh, Ayelech; Tora, Ephrem; Abayneh, Edget (Frontiers in Veterinary Science, 2022)
Background: Foot and mouth disease is extremely contagious viral disease of all cloven-hoofed animals which hampers the livestock production and productivity in Ethiopia. So, this cross-sectional study was conducted from January 2021 to December 2021 to estimate the seroprevalence of bovine foot and mouth disease and to assess farmers’ knowledge about the disease in selected districts of Gamo zone. Three districts and two kebeles from each district were purposively sampled. A simple random sampling technique was employed to select individual animals from each kebeles. A total of 384 sera samples were collected and concurrently 100 farmers were interviewed. The samples were tested using 3ABC ELISA for antibodies against nonstructural proteins of foot and mouth disease virus at national animal health diagnostic and investigation center. A univariable and multivariable logistic regression were used to analyze FMD associated risk factors. Result: The questioner survey result revealed that among the interviewed farmers, 66% had knowledge about the disease and 28% farmers reported having a case of FMD in at least one animal on their farm in the previous six months. The overall seroprevalence of foot and mouth disease was 26.8%. The multivariable logistic regression revealed that age, breed and agro-ecology had significant association with seropositivity of the animal. Higher seroprevalence (64.57%) was observed in low land followed by mid land (9.30%) and high land (5.88%). Study animals from low land areas were 9.26 times more likely to be seropositive (OR= 9.26, CI =2.22 - 38.62) for FMD than high land animals. Also, adult animals have a chance of 9.01 (OR=9.01, CI 3.18 - 25.53) more likely to be seropositive for the disease than young animals. The multivariable logistic regression revealed that cross breeds have 84.7% (OR=0.153, CI 0.028 - 0.82) lower likelihood to be seropositive to FMD than local breeds. Conclusion: The present study result confirms as FMD is highly prevalent in the study area where as farmers’ knowledge regarding the disease transmission and vaccine availability is minimum. Hence the regional concerned bodies should implement FMD vaccination campaign and create awareness for smallholder farmers regarding the disease transmission, vaccine schedule, and vaccination importance